New genus and species of Hexagenitidae (Insecta: Ephemeroptera) from Yixian Formation, China - Huang, Jiandong; Ren, Dong; Sinitshenkova, Nina D.; Shih, Chungkun (Zootaxa, 2007)
A new genus and two new species of the extinct family Hexagenitidae, Epicharmeropsis hexavenulosus gen. et sp. nov. and Epicharmeropsis quadrivenulosus sp. nov., are described from the Late Jurassic-Early Cretaceous Yixian Formation, Hebei and Liaoning Provinces in China. Detailed description and illustration of the specimens along with a brief review of Hexagenitidae are given. By comparing with the imago specimens of so-called Ephemeropsis which were previously reported from China, we believe these Ephemeropsis-like specimens should be placed into Epicharmeropsis gen. nov. and Ephemeropsis Eichwald could be absent in China.